Pengaruh Metode Latihan Taktis terhadap Keterampilan Shooting Bola Tangan Pada Siswa SMA Negeri 2 Klari - Dini Priandini; Citra Resita; Dhika Bayu Mahardhika (Peneliti.net, 2023)
The purpose of this study was to find out about the effect of tactical training methods on the handball shooting skills of extracurricular students at SMA Negeri 2 Klari. The method used in this paper is an experiment with the One-Group Pretest-Posttest design. Data analysis techniques used Prerequisite analysis tests, namely the normality test using the Shapiro-Wilk test, homogeneity test and statistical hypothesis testing using the t-test (Pairedt-test). The sample in this study were 20 students from SMA Negeri 2 Klari who were taken using total sampling technique. Based on the results of the study, it can be concluded that there is a t-test result with a sig.(2-tailed) value of 0.00 where the value is smaller than 0.05 (sig. <0.05) then Ha is accepted and Ho is rejected, which means that there is an effect of tactical training methods on handball shooting skills of SMA Negeri 2 Klari extracurricular students, this is also supported by a pretest average score of 17.35 and a posttest average of 30.85, a Mean Difference score of 13.5 is obtained, this shows that the tactical training method for shooting skills have a better effect if calculated by a percentage (37.5%) compared to before being given the tactical training method.